If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3m + -2) + -5 = 8 + -2(m + -4) Reorder the terms: (-2 + 3m) + -5 = 8 + -2(m + -4) Remove parenthesis around (-2 + 3m) -2 + 3m + -5 = 8 + -2(m + -4) Reorder the terms: -2 + -5 + 3m = 8 + -2(m + -4) Combine like terms: -2 + -5 = -7 -7 + 3m = 8 + -2(m + -4) Reorder the terms: -7 + 3m = 8 + -2(-4 + m) -7 + 3m = 8 + (-4 * -2 + m * -2) -7 + 3m = 8 + (8 + -2m) Combine like terms: 8 + 8 = 16 -7 + 3m = 16 + -2m Solving -7 + 3m = 16 + -2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2m' to each side of the equation. -7 + 3m + 2m = 16 + -2m + 2m Combine like terms: 3m + 2m = 5m -7 + 5m = 16 + -2m + 2m Combine like terms: -2m + 2m = 0 -7 + 5m = 16 + 0 -7 + 5m = 16 Add '7' to each side of the equation. -7 + 7 + 5m = 16 + 7 Combine like terms: -7 + 7 = 0 0 + 5m = 16 + 7 5m = 16 + 7 Combine like terms: 16 + 7 = 23 5m = 23 Divide each side by '5'. m = 4.6 Simplifying m = 4.6
| x^2(x-5)=-3 | | 0=4(5-x)8 | | 12-(2m+7)=2+3m-12 | | 2x+2+3x+4=180 | | -4x+5+2x=-15 | | 2(X+1)-6=3X-21 | | x+2.5=5 | | -1=-3+r | | -8(8x-2)+1=17-4x | | 5-2(-6)+2= | | 2(x+33)=22 | | 3x-7=-5x+19 | | 2x+9=2x+14 | | 13.30+3.9h=c | | 3(-8x-2)+3x=39-6x | | 3[1-2x]=3-6x | | 8y-16=72 | | -5=2.6+f | | 21=3x-7 | | 4w+3=w-15 | | 129-w=238 | | .07-.01(x+1)=-.02(3-x) | | -26=x-3 | | 9-5x-8x+2= | | 3+55a=3-36a | | -2c=7d-3 | | 3xsquared-15x=0 | | -5+2m=-2m-m | | 2(10+3x)=56 | | -5x-40=0 | | (sqrt(-1)-z)(1+2*sqrt(-1))+(1-zi)(3-4*sqrt(-1))-1-7*sqrt(-1)=0 | | 2x^2-38x+12=0 |